Lithistid spicules in the sediments of the Turonian Variegated Shale in the Silesian Nappe, Polish Outer Carpathians - Okoński, Szymon; Górny, Zbigniew; Bąk, Marta; Bąk, Krzysztof (Wydawnictwa AGH, 2014)
Turbiditic silty and sandy intercalations in the Turonian Variegated Shale from the Silesian Nappe (Polish Outer Carpathians) contain numerous sponge spicules among siliciclastic fine-grained particles. The highest amount of spicule admixture is nearly 50%. In such layers, they create spiculitic sublitharenite microfacies. These sponge spicules contain forms belonging mostly to the Lithistida group (97% of morphotypes), with a small admixture of spicules from the Hexactinellidae group. Tetraclones with a high content of different types of triaenes dominate among desmas, what indicates the dominance of sponges from subfamily Tetracladina. The preservation state of spicules is generally poor. The Variegated Shale deposits that contain the sponge spicules were accumulated in a deep sea basin, below the calcium compensation depth. Most probably, the spicules were derived from loose material accumulated earlier in various parts of the basin slopes, from which they were exhumed and again redeposited by turbidity currents during the Turonian times.
Geology, Geophysics & Environment
Keywords: sponge spicules; Lithistida; Turonian; Variegated Shale; Silesian Nappe; Outer Carpathians.